1990
DOI: 10.1017/s0950268800059331
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation amongst genotypically homogeneousLegionella pneumophilaserogroup 1 isolates: implications for the investigation of outbreaks of Legionnaires' disease

Abstract: SUMMARYOne hundred and seventy-nine isolates of Legionella pneumophila serogroup 1, obtained from a site associated with an outbreak of Legionnaires' disease, were examined by monoclonal antibody subgrouping, restriction fragment length polymorphism typing, restriction endonuclease analysis and plasmid content. Nine distinct phenotypes were detected but at the genotypic level all strains were closely related. The data presented indicate that phenotypic variation of a single parent strain can occur within an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…The latter strain differed from the strain from hospital water only at markers Lpms1 and Lpms4, which could mean that the strain is of a different origin or that it is a variant of the strain isolated from water. This is reminiscent of the results of Harrison et al (9), who suggested that phenotypic variation of a single parent organism could account for the phenotypically different strains isolated from a single cooling tower. A larger number of colonies isolated from water could have been analyzed by tandem repeat typing at the time of the infection (as shown in Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The latter strain differed from the strain from hospital water only at markers Lpms1 and Lpms4, which could mean that the strain is of a different origin or that it is a variant of the strain isolated from water. This is reminiscent of the results of Harrison et al (9), who suggested that phenotypic variation of a single parent organism could account for the phenotypically different strains isolated from a single cooling tower. A larger number of colonies isolated from water could have been analyzed by tandem repeat typing at the time of the infection (as shown in Fig.…”
Section: Discussionsupporting
confidence: 53%
“…There was, however, no difference in the PFGE and AFLP patterns, even in a single band. Such serologic subtype variations have been reported earlier (11,18,30). The question whether these different phenoms represent an environmentally induced phenotypic expression or are caused by a true genetic event preceding the serologic change (14,20,34) could for the first time be answered in the present (16,34).…”
Section: Discussionmentioning
confidence: 72%
“…The method has been used widely in the investigation of outbreaks and clusters of legionellosis in the UK [15, 17, 181. Although the discriminatory power of the RFLP technique appears to be good, giving an index of discrimination (IOD) [19] of 0.909, in practice it has been found that some RFLP patterns are seen more frequently than others (e.g., RFLP type 1 [15]). In 1995, Luck and colleagues [20] demonstrated that a panel of isolates obtained from a single source, and considered to be indistinguishable by RFLP typing [21], could be discriminated hrther by PFGE with S' I .…”
Section: Introductionmentioning
confidence: 99%